An effective trigger for energy release of vinylheptafulvene-based solar heat batteries. Issue 43 (16th May 2017) - Cacciarini, Martina; Vlasceanu, Alexandru; Jevric, Martyn; Nielsen, Mogens Brøndsted
Abstract : An efficient strategy to activate the release of energy in dihydroazulene/vinylheptafulvene systems is developed. Abstract : Stoichiometric copper(i ) tetrakis(acetonitrile) is found to activate the thermal ring-closure reaction of a series of high-energy vinylheptafulvene isomers to the corresponding low-energy and photoactive dihydroazulenes, allowing the release of energy upon request.